Morphology of male World Cup and elite speed climbers - Draga, Paweł; Baran, Paulina; Henry Maskell, John; Trybek, Paulina; Pandurevic, Dominik; Sutor, Alexander (Frontiers in Sports and Active Living, 2025)
AimsTo compare somatic characteristics and somatotypes of elite World Cup and national level speed climbers relative to general adult population norms, and to identify anthropometric traits that differentiate performance levels.Materials and methodsEighteen male speed climbers participated in the study, including 10 international level and 8 national level athletes. Anthropometric data were collected according to the ISAK protocol, and somatotype was determined using the Heath-Carter method. Statistical analyses included the Shapiro–Wilk test to assess normality, the Student’s t-test or Mann–Whitney U test to compare groups. Principal component analysis (PCA) to reduce dimensionality and identify body composition characteristics differentiating athletes by performance level, and Spearman’s rank correlation coefficient to examine relationships between variables.ResultsInternational climbers showed significantly lower body fat (6.46%±1.22% vs. 9.40%±1.46%), and higher lean body mass (93.5%±1.22% vs. 90.6%±1.46%). They exhibited wider biacromial breadth (42.98±1.98 cm vs. 41.03±1.18 cm), humeral breadth (7.67±0.40 cm vs. 6.93±0.50 cm), and femoral breadth (9.49±0.44 cm vs. 8.99±0.42 cm). Both groups presented an ectomorphic-mesomorphic somatotype, with international athletes displaying a significantly higher mesomorphic component (6.08±0.81 vs. 4.63±0.61).ConclusionsInternational climbers differ from national-level athletes by having lower fat mass, greater lean body mass, and greater skeletal breadth, including biacromial, humeral, and femoral widths. Both groups show substantial morphological differences compared to the general adult population. Differences in the breadth of the humerus and femur, as well as in biacromial width, may reflect specific adaptations to the load patterns typical of speed climbing. Athletes at the international level showed a more homogeneous somatic profile, indicating morphological optimization at the highest levels of performance. Traits considered important in other climbing disciplines were not found to be relevant in speed climbing. The results presented require verification in larger and more diverse groups of speed climbers. Nevertheless, with appropriate caution, they may serve as an initial reference point for talent identification and morphological optimization in speed climbing.